2016
DOI: 10.3389/fmars.2016.00006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Priming Effect in a Planktonic Estuarine Microbial Community

Abstract: The "priming effect," in which addition of labile substances changes the remineralization rate of recalcitrant organic matter, has been intensively studied in soils, but is less well-documented in aquatic systems. We investigated the extent to which additions of nutrients or labile organic carbon could influence remineralization rates of 14 C-labeled, microbially-degraded, phytoplankton-derived organic matter (OM) in microcosms inoculated with microbial communities drawn from Grove Creek Estuary in coastal Geo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Coffin et al ., ; Pearson et al ., ; Brady et al ., ; Mills et al ., ; Whaley‐Martin et al ., ); however, it only provides a snapshot and is unable to resolve the potential selectivity that may occur over the short time span of hours to days. Other experiments performed over these shorter intervals used isotopically‐labelled substrates (Benner et al ., ; Sun and Wakeham, ; Gontikaki et al ., ; van Nugteren et al ., ; Steen et al ., ). However, these studies added compounds of known accessibility at elevated concentrations and may not reflect their utilization at natural concentrations, or the accessibility of other compounds found in the sediment.…”
Section: Discussionmentioning
confidence: 97%
“…Coffin et al ., ; Pearson et al ., ; Brady et al ., ; Mills et al ., ; Whaley‐Martin et al ., ); however, it only provides a snapshot and is unable to resolve the potential selectivity that may occur over the short time span of hours to days. Other experiments performed over these shorter intervals used isotopically‐labelled substrates (Benner et al ., ; Sun and Wakeham, ; Gontikaki et al ., ; van Nugteren et al ., ; Steen et al ., ). However, these studies added compounds of known accessibility at elevated concentrations and may not reflect their utilization at natural concentrations, or the accessibility of other compounds found in the sediment.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a number of studies have investigated the prevalence of a priming effect in aquatic ecosystems (e.g., van Nugteren et al ., ; Guenet et al ., ; Kuehn et al ., ; Steen et al ., ). Various types of ecosystems (marine, lentic, lotic) and habitats (pelagic, hyporheic, sediments) have been tested, as well as different sources of LOM (carbohydrates, algae leachate, gastropod mucus, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…The timescale over which priming is measured is important when considering the quantitative relevance of priming with respect to DOC mineralization and CO 2 fluxes from aquatic ecosystems. Many aquatic studies on the priming effect that have reported evidence of priming describe the phenomenon as "apparent" or "transient" because, although they observed initial differences in DOC consumption between unamended and primed treatments, ultimately the amount of DOC consumed after about 1 month is not significantly different from background consumption (Steen et al, 2016;Textor et al, 2018).…”
Section: No Priming Effect In Permafrost-influenced Watershedsmentioning
confidence: 99%